Out-of-phase thermo-mechanical fatigue crack growth and the effect of the compressive minimum load level on crack closure at notches. (December 2020) - Almroth, P.; Gustafsson, D.; Loureiro Homs, J.; Simonsson, K.
Highlights: OP TMF and isothermal room temperature crack growth experiments are carried out. OP crack growth rate is higher than isothermal crack growth rate for similar loading. In OP TMF there will be a tension-compression yield stress differential. FE modeling is used to study effect of yield stress differential on crack closure. Plasticity induced crack closure can explain the higher growth rates in OP TMF. The observed behavior can be modeled by an extension of the analytical Newman model. Abstract: Fatigue crack growth rate in Room Temperature and Out-of-Phase Thermo-Mechanical Fatigue notched specimen experiments on the nickel-base alloy IN792 is studied. It is shown that it is possible to explain the observed higher crack growth rate in OP TMF compared to RT testing for the same external load, if plasticity induced crack closure is considered. Modeling utilizes node-release finite element simulations with a temperature dependent yield stress, resulting in different yield stress in tension and compression. It is shown that a simple extension of the analytical Newman crack closure equation can describe the opening level in the performed experiments.